2021
DOI: 10.1182/bloodadvances.2020002790
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose decitabine for refractory prolonged isolated thrombocytopenia after HCT: a randomized multicenter trial

Abstract: Refractory prolonged isolated thrombocytopenia (RPIT) is an intractable complication after allogeneic hematopoietic cell transplantation (HCT), which often leads to poor prognosis. A clinical study was designed to validate the efficacy and safety of low-dose decitabine for RPIT after HCT and explore the related underlying mechanisms. Eligible patients were randomly allocated to receive 1 of 3 interventions: arm A, low-dose decitabine (15 mg/m2 daily IV for 3 consecutive days [days 1-3]) plus recombinant human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…Of the multilineage reconstitution, platelet delayed recovery is the main concern, which accounts for 20%-37% of HSCT recipients. 30 Our data showed a platelet reconstitution advantage in decitabine and NAC treated cohort, with more patients in Arm A achieving a platelet count above 50 Â 10 9 /L. The improved hematopoietic reconstitution after NAC treatment was considered to be associated with repaired bone marrow microenvironment (i.e., endothelial cells and mesenchymal stem cells function) in previous studies.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Of the multilineage reconstitution, platelet delayed recovery is the main concern, which accounts for 20%-37% of HSCT recipients. 30 Our data showed a platelet reconstitution advantage in decitabine and NAC treated cohort, with more patients in Arm A achieving a platelet count above 50 Â 10 9 /L. The improved hematopoietic reconstitution after NAC treatment was considered to be associated with repaired bone marrow microenvironment (i.e., endothelial cells and mesenchymal stem cells function) in previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, we included NAC in the traditional mBUCY regimen. Of the multilineage reconstitution, platelet delayed recovery is the main concern, which accounts for 20%–37% of HSCT recipients 30 . Our data showed a platelet reconstitution advantage in decitabine and NAC treated cohort, with more patients in Arm A achieving a platelet count above 50 × 10 9 /L.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This outcome indicated that patients with sufficient MKs in the BM were more likely to benefit from avatrombopag, and for those with decreased MKs in the BM, or refractory to other therapies, low-dose DAC would be recommended. 31,32…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the problem of lineage recovery failure in HSC-based therapy, especially the Mk lineage, have called the demand for the study of HSCs function maintenance 6 . Patients who fail in Mk lineage reconstitution after transplantation need to rely on platelet transfusion, which is a heavy financial and physiological burden 7 9 . However, the strategy of “high-fidelity” expansion of HSCs with self-renewal and Mk-lineage reconstruction ability has yet to be optimized.…”
Section: Introductionmentioning
confidence: 99%